Effects of Different Growth Media on In Vitro Seedling Development of an Endangered Orchid Species Sedirea japonica - Jiae An; Pyoung Beom Kim; Hyeong Bin Park; Seongjun Kim; Hwan Joon Park; Chang Woo Lee; Byoung-Doo Lee; Nam Young Kim; Jung Eun Hwang (Plants, 2021)
Sedirea japonica is becoming endangered, and even extinct, due to habitat destruction and illegal collection, and the development of an optimized artificial propagation system is necessary for its conservation and reintroduction. Thus, the effects of plant growth medium strength (Murashige and Skoog (MS) and Hyponex media) and the addition of activated charcoal (AC) and organic supplements on seedling growth of S. japonica were investigated through in vitro seed culture. The results showed that seedling growth was higher in half-strength (1/2) media than in full-strength media. After the addition of AC, the highest leaf area (2.14 cm2) was recorded in the seedlings grown in 1/2 Hyponex medium, and after the addition of organic supplements, root development increased regardless of the media type. Among the sixteen suitable media tested at later seedling growth stages, 1/2 MS medium with the addition of 0.6 g·L−1 AC, 30 g·L−1 banana homogenate and 10 g·L−1 apple homogenate was generally effective in fresh weight (6.13 g) and root length (9.59 cm). We demonstrated which organic supplements are preferred for in vitro growth of seedlings developed from S. japonica protocorms by asymbiotic seed culture, which can be used for mass production and conservation of this rare epiphytic orchid.